2018
DOI: 10.3389/fphys.2018.00946
|View full text |Cite
|
Sign up to set email alerts
|

Replicability of Physical Exercise Interventions in Lung Transplant Recipients; A Systematic Review

Abstract: Introduction: This systematic review aimed to assess the replicability of physical exercise interventions in lung transplantation patients. For replicability we focused on (1) the description of training principles, (2) the description of FITT components and adherence to the interventions, (3) the amount of detailed information given on the physical exercise intervention, and (4) reporting the methodological quality of the included works.Methods: Relevant databases (Medline-Ovid, EMBASE, CINAHL, PsychInfo, Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…We identified 7804 studies and included 28 systematic reviews18–20 22 24 34 35 37–57 (figure 1). These 28 reviews included 1467 studies comprised of 1724 interventions.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 7804 studies and included 28 systematic reviews18–20 22 24 34 35 37–57 (figure 1). These 28 reviews included 1467 studies comprised of 1724 interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other systematic reviews on exercise training in headache patients have found a low replicability. 34,43 Indeed, lack of replicability is an important problem facing pain science and research. It is therefore necessary that future clinical trials in primary headaches address more adequately this aspect to improve aplicability.…”
Section: Discussionmentioning
confidence: 99%
“…It assesses the risk of bias coming from the reporting of information, external and internal validation, and power. Some modifications were applied to improve the scoring system, as used previously (Knols, Fischer, Kohlbrenner, Manettas, & de Bruin, 2018). The scoring represents the percentage of criteria properly fulfilled.…”
Section: Methodsmentioning
confidence: 99%